An open-label antacid-controlled randomized trial on effectiveness of alginate-antacid preparation (Gaviscon®) in suppression of post-supper acid-pocket, night-time acid-reflux and symptoms in asymptomic obese participants - Deraman, Mohd Adli (2017)
Gastroesophageal reflux disease [GERD] with symptoms of heartburn and acid regurgitation are a common disorder in Asian population especially in overweight and obese persons. Acid pocket in the proximal part of stomach after meals has been shown to be an important mechanism of GERD.The acid pocket is increasingly recognized as a source from which acid reflux events originate. The presence of this gastric acid pocket has become an attractive therapeutic target. Proton pump inhibitors have been shown to reduce acidity of the acid pocket however alginate antacid formulation is inconsistent effects have been reported. The alginate-antacid formulations are used for the symptomatic treatment of GERD and appear to act by a unique mechanism which differs from other groups traditional antacids.